Нічниця довговуха та кажан північний (Mammalia, Chiroptera) на Заході України - Покиньчереда, В.Ф.; Загороднюк, І.В.; Постава, Т.; Лабоха, М.; Покиньчереда, В.В. (Вестник зоологии, 1999)
Нові знахідки рідкісних видів кажанів на заповідних територіях Східних Карпат отримано із застосуванням ультразвукових детекторів (E. nilssoni) та хіро-птерологічних тенет (M. bechsteini). Наведено результати аналізу всіх відомих знахідок цих видів в західних областях України як в просторі, так і в часі. Сучасне поширення Myotis bechsteini пов'язано з ареалами буків (Закарпаття, Прикарпаття та Поділля), ареал Eptesicus nilssoni пов'язаний з бореальними угрупованнями Полісся й Карпат. Myotis bechsteini — рідкісний вид з відносно сталою чисельністю; Eptesicus nilssoni має стійку тенденцію до зниження населення та скорочення ареалу. Новые находки редких видов рукокрылых на заповедных территориях Восточных Карпат получены с использованием ультразвуковых детекторов (E. nilssoni) и ловчих сетей (M. bechsteini). Приведены результаты анализа всех известных находок этих видов в западных областях Украины как в пространстве, так и во времени. Современное распространение Myotis bechsteini связано с ареалами буков (Закарпатье, Прикарпатье и Подолия), а ареал Eptesicus nilssoni связан с бореальными сообществами Полесья и Карпат. Myotis bechsteini — редкий пид с относительно устойчивым обилием, а Eptesicus nilssoni характеризуется постоянным снижением численности и сокращением ареала. Information on new findings of two rare bat species on the reserved massifs of the Eastern Carpathians is given. New records were obtained using bat detector (E. nilssoni) and bat nets (M. bechsteini). Analysis of all known records of these species in the western regions of Ukraine in a space as well as in a time is given using original, literature and museum data. Modern distribution of Myotis bechsteini is related with the range of beech forests (Transcarpathians, Northern Carpathians and Podillia), and range of Eptesicus nilssoni is related with boreal communities of Polissia and Carpathians. Both species are the most rare and endangered bat species in the Ukrainian fauna, and they need protection. Myotis bechsteini is rare species with relatively stable abundance, and Eptesicus nilssoni is characterized by population decline.